Analisis Pesan dan Persepsi Konsumen terhadap Iklan TV Aqua Pasca Boikot Produk Terafiliasi Israel - Prastari, Aprilina; Gaib, Wafa Auliya Insan (Universitas Muhammdiyah Yogyakarta, 2025)
The Israeli occupation of Palestine has been ongoing since 1948. After decades of military aggression, tensions escalated in October 2023 and continued up to the time of this article's writing in March 2025—marking over a year of brutal attacks. One of the major protest movements that gained momentum since October 2023 has been the boycott of brands affiliated with Israel. One such brand is Aqua, a bottled water product whose producer, Danone, is affiliated with Israel. In response to the widespread boycott, Aqua released a